2006
DOI: 10.1177/205873920601900110
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HECA-452 in Parapsoriasis and Mycosis Fungoides

Abstract: We have investigated the HECA-452 expression in large plaque parapsoriasis (PP) and mycosis fungoides (MF) patients, evaluating the potential role of this biomarker in both cutaneous disorders. Skin specimens from 72 PP and 61 MF patients were selected in this study. We compared their actual histological diagnosis with their previous diagnosis and we found that all 72 PP patients had the same diagnosis as before (stable PP), while 26 out of 61 MF have a previous PP histological diagnosis (evolving PP). Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…I) (II). The literature is not without data on the characteristics of multipotential stromal cells deriving from bone marrow (BMSCs) and their potential development into osteoblasts, chondrocytes, adipocytes and perhaps even into muscle and neural tissues (12)(13)(14)(15)(16)(17); they are also characterized by their high proliferative capacity ex vivo and differentiation in multiple lines of cells according to the micro-environmental conditions in which they are cultivated. By analogy, it is possible to speculate that tissues taken from DPCs, from exfoliated deciduous teeth (EDCs) and from PDLCs contain a population of multi potential formative cells.…”
mentioning
confidence: 99%
“…I) (II). The literature is not without data on the characteristics of multipotential stromal cells deriving from bone marrow (BMSCs) and their potential development into osteoblasts, chondrocytes, adipocytes and perhaps even into muscle and neural tissues (12)(13)(14)(15)(16)(17); they are also characterized by their high proliferative capacity ex vivo and differentiation in multiple lines of cells according to the micro-environmental conditions in which they are cultivated. By analogy, it is possible to speculate that tissues taken from DPCs, from exfoliated deciduous teeth (EDCs) and from PDLCs contain a population of multi potential formative cells.…”
mentioning
confidence: 99%
“…In addition to acute inflammatory responses, PMN appear to be involved in the pathogenesis of acute and chronic inflammatory disorders [35][36][37] . RANTES and MCP-1 ␤ chemokines are potent chemoattractants for mast cells and have histamine-releasing activity comparable with that of anti-IgE [9][10][38][39][40] . We have previously shown that chemokines (C-C) such as MCP-1 and RANTES induce steady-state levels of histidine decarboxylase (HDC) mRNA in basophilic cells in vitro and in vivo and recruited mast cell mediation of allergic inflammation [9,10] .…”
mentioning
confidence: 99%
“…EBV-infected B cells widely express MHC-II molecules and activate CD4+ T cells. EBV-specific CD4+ T cell responses are readily identifiable against soluble lytic antigens (BZLF1, BMLF1, and BCRF1), the envelope components (gp350 and gp110) [56][57][58][59][60], and the potential latent antigens (EBNA 1, 2, 3C, and LMP2) [48]. CD4+ CTLs recognize antigens in EBV lytic/latent phases and kill infected B cells and LCLs through Fas/FasL interactions [61].…”
Section: Cellular Immune Responsesmentioning
confidence: 99%